Hubungan antara Burnout dengan Self Efficacy pada Perawat Di Ruang Rawat Inap RSUD Prof. Dr. Margono Soekarjo Purwokerto - Sulistyowati, Priyatin (Jurnal Keperawatan Soedirman, 2007)
Burnout is the condition in which the person has the physical, mental and emotional tiredness, it happens because of the stress in a long time / term. It also requires the activity of the high emotion. Burnout can be minimized by high self efficacy of the related person. Dealing with the health service especially in the hospital, nurse is the most potential person who deals with burnout among the other health services. The nurse has the burnout because she / he contact with the patients during 24 hours. It is the longest period in his / her job. Burnout can decrease the ability of the nurse in his / her work, for instances he / she has no spirit in his / her activity, She / he can be disturbed her / his emotion easily. The purpose of this research is to know the relationship between self efficacy with the degree of burnout faced by the nurse in the hospitalized care room of Prof. Dr. Margono Soekarjo Purwokerto. The whole samples are 100 nurses who work in 12 hospitalized care rooms (N = 100 ) The result of this research shows that the variable of self efficacy is that empirical mean (x = 78,63) in bigger than hypothetical mean (x = 67,5).This case shows that the self efficacy of the nurse in executing the care in the hospital tends increasing in high degree. The variable of empirical mean of the burnout is x = 60,56, and hypothetical mean is x = 75. It means that the low relative subject has the burnout in executing the work